2015
DOI: 10.4236/oalib.1101783
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spirituality on Quality of Life of Patients with Chronic Kidney Disease and Its Correlation with the Mental Health Status and Cognitive Perception for Their Illness. Study Protocol

Abstract: Background: Patients who suffer from chronic renal disease face problems in many aspects of their life, problems that are physical, social as well as mental, such as stress, anxiety, depression. Patients with Chronic Kidney Disease (CKD) exhibit a number of spiritual needs, which relate to and influence the psychological adaptation to the illness. Aim: The aim of the present study is to investigate spirituality and spiritual needs of patients with CKD and the possible relation between spirituality, quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
3
1
Order By: Relevance
“…This result is in opposition to various studies in the international literature [26]. Although a recent study in Greece among hemodialysis patients also reported good levels of QoL among the patients, the variety of results can be attributed to cultural factors as well as the family structure and enhanced social support that patients can have in other cultures [27]. In the present study, 23.8% of the participants suffered from anxiety and 18.6% from depression.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in opposition to various studies in the international literature [26]. Although a recent study in Greece among hemodialysis patients also reported good levels of QoL among the patients, the variety of results can be attributed to cultural factors as well as the family structure and enhanced social support that patients can have in other cultures [27]. In the present study, 23.8% of the participants suffered from anxiety and 18.6% from depression.…”
Section: Discussioncontrasting
confidence: 99%
“…The Impact on Daily Life included improved coping mechanisms, lifestyle changes, enhanced emotional wellbeing, better interpersonal relationships, increased life satisfaction, and engagement in meaningful activities. These findings resonate with the work of Fradelos et al (2015), who observed that spirituality positively influenced the quality of life in patients with chronic kidney disease (Fradelos et al, 2015).…”
Section: E-issn: 3041-8542supporting
confidence: 88%
“…Empirical studies have consistently demonstrated the beneficial effects of spirituality on coping with chronic illness. For example, Fradelos et al (2015) examined the effect of spirituality on the quality of life of patients with chronic kidney disease, revealing a positive correlation between spiritual practices and mental health status (Fradelos et al, 2015). Similarly, Harbali and Koç (2021) found that spiritual orientation and religious coping significantly alleviated psychosocial problems among oncology patients (Harbali & Koç, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Those bio-physiological changes have serious social consequences and impact on the daily lives of the individual’s social relations, identity and sense of self. Moreover they face problems in many aspects of their life, physical and social problems as well as mental such as stress, anxiety and depression ( 12 - 15 ). Studies on patients with CKD in regard with the spirituality, led to the conclusion that these patients declare an amount of spiritual needs, which relate and influence the psychological adjustment to the illness.…”
Section: Introductionmentioning
confidence: 99%